An Exploration of the Experiences and Perceptions of TBI Survivors About Accessing Vocational Rehabilitation During the COVID-19 Pandemic - Tarryn Petersen; Mogammad Shaheed Soeker (Occupational Therapy International)
Conclusion: The study found that there were barriers and facilitators to accessing occupational therapy rehabilitation during the COVID-19 pandemic for TBI survivors. More research needs to be conducted to explore the efficacy of telehealth/telemedicine for occupational therapy rehabilitation and the role of the occupational therapist in global pandemics.